PATRIARCHY AND THE NOTION OF CHILDLESSNESS IN AYOBAMI ADEBAYO’S STAY WITH ME - Ibanga, Grace Itoro (International Journal of Humanity Studies (IJHS), 2025)
The essence of this study is to portray the patriarchal attitudes and tendencies towards the notion of childlessness in certain Nigerian families. The study used content analysis in Ayobami Adebayo’s novel Stay with Me (2017), employing the theoretical frameworks of patriarchy and childlessness to trace the extent to which the disease of childlessness in marriages hinges on the collective patriarchal domineering authority to impose psychological trauma on the “claimed barren woman”. Findings revealed that most infertility in marriages is more common in men than women. However, since the Nigerian cultures are biased against women, they compel them to tolerate the denunciations of sterility, even when there is substantial evidence of the man's sterility displayed all over. The study opines that although childlessness may acquire a sociological or cultural viewpoint, it is purely biological and medical problems, which should not attract superstition and diabolic means to proffer solutions. The study recommends that researchers in human health sciences proffer solutions by creating awareness and supplying adequate, comprehensive treatments to people living with sterility syndrome in Nigeria. Again, the Nigerian government should bring in medical experts from the international community to rehabilitate the victims of childlessness by proffering lasting solutions.